Indigenous perspectives on marital dynamics: A qualitative study of Sotho couples’ experiences with customary marriage, stressors, strengths and indigenous marital counselling - Phakane, Tankiso; Goliath, Veonna (Social Work/Maatskaplike Werk, 2025)
The study, motivated by higher divorce rates in customary marriages compared to statutory ones in a rural Eastern Cape village, critiques the dominance of Western paradigms in social sciences that marginalise African worldviews. By applying the theory of social constructionism, it explores the stressors and strengths of customary marriages, and the value of indigenous counselling through the narratives of Sotho couples. A qualitative narrative research design was employed, involving 20 participants in customary marriages for 20 twenty years, selected through non-probability purposive sampling. Data were collected through separate focus group interviews for males and females, with thematic analysis used to generate themes for analysis. Findings indicate that customary marriage preserves cultural identity, spiritual unity, and kinship. However, modern influences such as globalisation and women’s empowerment challenge these traditions, contributing to marital stressors. Despite gender equality reforms, patriarchal norms often disempower women and children. Indigenous counselling, rooted in humanism, involves elders and community leaders in conflict resolution, promoting collective responsibility, strengthening bonds and fostering resilience. The study advocates for incorporating indigenous knowledge into social work practice to improve support for Sotho couples, enhance their wellbeing and reinforce cultural resilience.